Analisis Pengaruh Pelatihan, Bantuan Modal, dan Cara Pengelolaan Usaha Terhadap Pendapatan Usaha Mikro Kecil dan Menengah - Mei Rani Amalia (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2018)
Micro, Small, and Medium Enterprises (MSME) scale have an important role for the national income in Indonesia. They were proved – could be survive while the country had economic crisis. This study aims to determine analysis the influence of training, capital, and the managerial empirically to MSME income (case study to MSME of batik centre). This research used 60 samples with purposive random sampling technique. Data were collected through observation, interview, and questionnaires. The analysis method of this research is linear multiple regression. The results of the analysis indicate that partially and simultaneously independent variables affect MSMEs income.